Investigation of casting quality change of A356 by duration in liquid state - Uludağ, Muhammet; Gurtaran, M.; Dispinar, D. (Springer International Publishing, 2019)
This study aims to investigate how casting quality change in aluminum melt during the holding period in liquid state. 10 kg of ingot was melted in a SiC crucible by using an electrical furnace. A sample was taken every five minutes from 0 to 55 min after the alloy was melted. Reduced pressure test (RPT) samples were collected to be solidified under 80 mbar. All samples were sectioned into two parts vertically, and one of them was prepared for metallographic examination. Surface of the samples was subjected to image analysis by using via image analysis software. Bifilm index and bifilm area were analyzed in detail. As a result, it can be concluded that first 30 min of liquid metal is important, because casting quality tends to get worse after 30 min. © The Minerals, Metals & Materials Society 2019.
Keywords: A356 alloy; Bifilms; Casting quality; Holding time